2020
DOI: 10.1002/ece3.6481
|View full text |Cite
|
Sign up to set email alerts
|

The frugivory network properties of a simplified ecosystem: Birds and plants in a Neotropical periurban park

Abstract: Frugivory networks exhibit a set of properties characterized by a number of network theory‐derived metrics. Their structures often form deterministic patterns that can be explained by the functional roles of interacting species. Although we know lots about how these networks are organized when ecosystems are in a complete, functional condition, we know much less about how incomplete and simplified networks (such as those found in urban and periurban parks) are organized, which features are maintained, which on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
(115 reference statements)
1
3
0
Order By: Relevance
“…Associated with empirical studies that found high resources partitioning among frugivores in unmanaged peri-urban forest patches (Corral et al 2020, Salazar-Rivera et al 2020, these results reinforces the value of unmanaged forest patches within urban areas for interaction stability. Therefore, patches of natural areas favor frugivore animals and are essential for maintenance of seed dispersal interactions.…”
Section: Spatial Variationsupporting
confidence: 75%
“…Associated with empirical studies that found high resources partitioning among frugivores in unmanaged peri-urban forest patches (Corral et al 2020, Salazar-Rivera et al 2020, these results reinforces the value of unmanaged forest patches within urban areas for interaction stability. Therefore, patches of natural areas favor frugivore animals and are essential for maintenance of seed dispersal interactions.…”
Section: Spatial Variationsupporting
confidence: 75%
“…Urban and periurban greenspaces preserve fundamental ecological interactions, many of them deeply shaped by human management and activity (Gasperin and Pizo, 2009). While we know some characteristics of these networks, e.g., urban greenspaces as environments that favor generalist species, capable of exploiting available resources broadly and effectively (Clavel et al, 2011;Machado-de-Souza et al, 2019;Palacio, 2019;Salazar-Rivera et al, 2020;Schneiberg et al, 2020), we also know little about many other features, such as the ones explored in this paper. We consider our understanding of how birdplant frugivory interactions are structured and organized in cities will benefit from including extrinsic factors such as those considered in spatial analyses.…”
Section: Unforeseen Extrinsic Factors and Caveatsmentioning
confidence: 96%
“…One related factor with known effects in fruit consumption by birds is their morphologic matching: altered environments generally do not have fruits of large sizes and those present therein have a lower dispersal probability because their largesized frugivores are more likely to be absent in these habitats (Galetti et al, 2013;Emer et al, 2018). Urban environments tend to have a low number of species and interactions, resulting in simplified plant-bird frugivory and pollination networks dominated by generalists (Maruyama et al, 2019;Salazar-Rivera et al, 2020;Schneiberg et al, 2020). Conversely, forest cover and connectivity are key in the maintenance of interaction diversity in seed dispersal networks (Monteiro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Provisioned food in the form of spatially expansive resources such as agricultural resources, plantations, orchards, gardens can change species richness and functional diversity of animals to simplified animal communities comprising species suited to farmland or urban dwelling and can thus homogenize plant–animal interactions (Salazar‐Rivera et al 2020). These changes in plant and animal communities (Galbraith et al 2015) can greatly modify seed dispersal networks and reduce their resilience due to losses of functional diversity and homogenization of flora (Bastazini et al 2019).…”
Section: Changes In Plant Communitiesmentioning
confidence: 99%